The Effect of the 17th April 2019 Election on Stock Prices on the Indonesia Stock Exchange - Sri Hartono; Rosa Nikmatul Fajri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Inter-party coalition is also inevitabel where with a good coalition will affect the macro economy of government work is quite good, characterized by increasing GDP per capita from year to year, controlled inflation in recent years, the ranking of debt securities that received investment grade , the debt to GDP ratio is relatively lower than other countries, interest rates continue to decline, there is progress in combating corruption. Investment grade is one of the activities contained in the capital market as a measure of the health of the economy which raises investors' enthusiasm to return to invest. Historical statistics 2003-04 and 2008-09, one year before the general election (election) usually the share price represented by the CSPI one time experienced a significant increase which rose 62.82% in 2003 and fell significantly namely -50.64% in 2008 and the same event also applies to government bonds, which rose 16.07% in 2003 and was relatively flat by -0.03% in 2008 after experiencing a significant decline in October - November. This study aims to determine the effect of the April 17, 2019 general election on stock prices on the Indonesia Stock Exchange. This study took a sample at the stage during the event period (event period) by utilizing the abnormal return situation. The research method that will be used is the event study method regarding political events or general elections by looking at the movement of stock prices on the Indonesia Stock Exchange. Data analysis in this study used Microsoft Excel software and SPSS. The results of this study are the return per day before the ten days of the April 2019 election and the return per day after the ten days of the April 2019 election does not affect the stock prices listed on the stock exchange, especially in companies listed in LQ-45 and if judging in terms of abnormal returns also do not has a significant influence on stock prices before and after the ten days of holding elections in April 2019. Keywords: Indonesia Stock Exchange, Stock Price, Abnormal Return, LQ-45